SALOMON-N2: balloon-borne experiments, atmospheric compounds measurements, flight of 25 August 2009 - Gwenael, Berthet (AERIS, 2021)
SALOMON-N2 (Spectroscopie d'Absorption Lunaire pour l'Observation des Minoritaires Ozone et Nox - Nacelle 2) is a UV-visible balloon-borne spectrometer designed, like SALOMON, to acquire vertical profiles of ozone, nitrogen, chlorine and bromine species and the extinction coefficient of aerosols, at altitudes between 15 and 40 km. The instrument weighs about 170 kg. It works in automatic mode during flight (including start-up, pointing, spectre acquisition and shut-down). The pointing system, the pivot and the gondola were developed at the Laboratoire de Physique et Chimie de l'Environnement (LPCE). Salomon-N2 uses an spectrometer similar to the one used in the SAOZ instrument and an aerosol counter called STAC. Payload landing place: near Nedre Soppero, 57 km NE from Kiruna, Sweden. This flight is involved in the STRAPOLETE campaign.